KONSEPSI KEPEMIMPINAN PENDIDIKAN - Kustutik Kustutik (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2018)
In perspective educational, dominant factor of educational is the concept of development . In the components engaged in educational development are identified by the presence of an intense educational organization overseeing and evaluating course of educational process as well as change the value of education from time to time. As well as less conducive competition between organizations and the loss of the original character of institutions due to social and technological developments. Moreover, it will affect the changes to induvidualism and disintegration problems. Therefore, a proper way or management is needed to "play" in educational development process. As well as manager of an education, the leader or leader must be able to keep moving to adjust development of time.